NKG2C Natural Killer Cells in Bronchoalveolar Lavage Are Associated With Cytomegalovirus Viremia and Poor Outcomes in Lung Allograft Recipients. Issue 3 (March 2019) - Calabrese, Daniel R.; Chong, Tiffany; Wang, Angelia; Singer, Jonathan P.; Gottschall, Marc; Hays, Steven R.; Golden, Jeffrey A.; Kukreja, Jasleen; Lanier, Lewis L.; Tang, Qizhi; Greenland, John R.
Abstract : Background: Cytomegalovirus (CMV) infection is a risk factor for chronic lung allograft dysfunction (CLAD), which limits survival in lung allograft recipients. Natural killer (NK) cells that express the NKG2C receptor mediate CMV-specific immune responses. We hypothesized that NKG2C + NK cells responding to CMV in the lung allograft would reduce CMV-related inflammation and would improve CLAD-free survival. Methods: We prospectively followed 130 subjects who underwent lung transplantation from 2012 to 2016. Bronchoalveolar lavage (BAL) NK cells were immunophenotyped for NKG2C, maturation, and proliferation markers. CMV viral load, serologies, serial spirometry, and mortality were recorded from medical records. Natural killer cell subset association with CMV endpoints were made using generalized estimating equation-adjusted linear models. BAL NKG2C + NK cell association with CLAD-free survival was assessed by Cox proportional hazards modeling. Results: NKG2C + NK cells were more mature and proliferative than NKG2C − NK cells and represented a median of 7.8% of BAL NK cells. The NKG2C + NK cell proportion increased prior to the first detection of viremia and was nearly tripled in subjects with high level viremia (>1000 copies/mL) compared with no detected viremia. Subjects with increased BAL NKG2C + NK cells, relative to the median, had a significantly increased risk for CLAD or death (hazard ratio, 4.2; 95% confidence interval, 1.2–13.3). Conclusions: The BAL NKG2C + NK cell proportion may be a relevant biomarker for assessing risk of CMV viremia and quantifying potential CMV-related graft injury that can lead to CLAD or death.